2016
DOI: 10.1108/lr-06-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Understanding research students’ behavioural intention in the adoption of digital libraries

Abstract: Purpose The purpose of this study is to investigate the factors that influence the adoption of Higher Education Commission (HEC) National Digital Library among research students in different universities of Pakistan. Design/methodology/approach The study framework was based on technology acceptance model (TAM). A sample of Pakistani university students completed the questionnaire measuring the effects of extraneous stimuli through cognitive responses on adoption of the HEC digital library. To test the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 56 publications
2
39
2
1
Order By: Relevance
“…Regarding the path of SN->PE, the analysis revealed that the SN factor had an insignificant effect on performance expectancy (β = 0.05, P > 0.05) hence, H9 was not supported. This result was unexpected and is contrary to prior research findings, e.g., Khan and Qutab (2016) in which the system navigation significantly predicted the users' perceived usefulness. Nonetheless, in an e-library system, navigation was found to have an insignificant influence on the perceived usefulness (Jeong, 2011).…”
Section: Behavioural Intention (Bi )contrasting
confidence: 99%
“…Regarding the path of SN->PE, the analysis revealed that the SN factor had an insignificant effect on performance expectancy (β = 0.05, P > 0.05) hence, H9 was not supported. This result was unexpected and is contrary to prior research findings, e.g., Khan and Qutab (2016) in which the system navigation significantly predicted the users' perceived usefulness. Nonetheless, in an e-library system, navigation was found to have an insignificant influence on the perceived usefulness (Jeong, 2011).…”
Section: Behavioural Intention (Bi )contrasting
confidence: 99%
“…The 40 students expressed the importance of reaching the desired information easily and efficiently. In respect to digital libraries, Pakistani students said that SN has a positive impact on their perceived ease of use and perceived usefulness (Khan & Qutab, 2016). In e-commerce, Green and Pearson (2011) established the effect of navigation on the perceived usefulness of online shopping websites using 344 undergraduate students.…”
Section: System Navigationmentioning
confidence: 99%
“…For example, Matzat and Sadowski (2012) found that individuals with the essential computing skills engage more with the Internet than those with weak computing skills. A recent survey on the usage of digital libraries reported computer self-efficacy as a significant determinant of computer usage (Khan and Qutab, 2016).…”
Section: Ability and Usagementioning
confidence: 99%